Comparative investigations of structure and properties of micro-arc wollastonite-calcium phosphate coatings on titanium and zirconium-niobium alloy - Sedelnikova M. B. Mariya Borisovna; Komarova E. G. Elena Gennadjevna; Sharkeev Yu. P. Yury Petrovich; Tolkacheva T. V. Tatjyana Viktorovna; Khlusov I. A. Igor Albertovich; Litvinova L. S. Larisa Sergeevna; Yurova K. A. Kristina Alekseevna; Shupletsova V. V. Valeria Vladimirovna (2017, 2017)
Title screen